2013
DOI: 10.1039/c2em30758h
|View full text |Cite
|
Sign up to set email alerts
|

Microbial exposure and respiratory dysfunction in poultry hatchery workers

Abstract: Today's modern animal confinement with high stocking density of a single species has resulted in new workplaces that are rarely characterised in regard to microbial exposure. In this study we determine the personal microbial exposure by long term monitoring in a duck hatchery. Four hatchery workers were accompanied for four weeks and on every working day personal bioaerosol sampling and lung function tests were performed. Quantitative and qualitative molecular methods were used for analysing bioaerosol samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A German study demonstrated a decrease in FEV 1 for days involving duckling sorting, but not for the days without [10]. Although the sample included only four workers, this result suggests that airborne particles from duckling down have a negative effect on respiratory health.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A German study demonstrated a decrease in FEV 1 for days involving duckling sorting, but not for the days without [10]. Although the sample included only four workers, this result suggests that airborne particles from duckling down have a negative effect on respiratory health.…”
Section: Discussionmentioning
confidence: 90%
“…Among them, farm managers and workers in the hatchery sector (about 6,500 people) are occupationally exposed to bioaerosols due to bird movements or animal handling. Few studies have been published on hatcheries [8,9,10]. Furthermore, initial observations indicate that bacterial contaminant concentrations are higher in the air of duck hatcheries than in chicken hatcheries [11,12], although these studies were limited to a single premises in Germany and in Bulgaria.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate possible reservoirs in future studies, the environment of one-day-old chicks, i.e., hatcheries and transport vehicles, should be analysed. In other studies, A. baumannii isolates have been found in the air of a duck hatchery [ 27 ] and non-sterile water (which is used for humidity regulation during the brood), which has been suggested to be a possible source of contamination in hatcheries [ 26 ]. Moreover, feather down has also been considered as a potential carrier [ 26 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been detected in the air of a duck hatchery. The authors considered that these bacteria might be a possible trigger for respiratory diseases in hatchery workers [ 26 , 27 ]. Liu et al also point out that cross-infections between humans and chicks through handling may be possible [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This problem is particularly acute in tropical and subtropical countries, where people often come in contact with numerous parasites and inhale harmful bioaerosols [ 3 , 4 , 5 ]. In the temperate zone, a significant number of cases of diseases caused by biological factors is observed, not only among health professionals [ 6 ] and dentists [ 7 ], but also people employed in agricultural production [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], wood industry [ 15 , 16 ], composting plants [ 17 , 18 , 19 ], sewage and solid waste treatment plants [ 20 , 21 ], and the dairy industry [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%